Muscular contributions to center of mass acceleration during countermovement jumps - Kipp, K.; Kim, H. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to study the contributions of individual leg muscles and muscle groups to accelerate the body`s centre of mass (COM) during countermovement jumps (CMJ). Ten NCAA college basketball players performed maximal effort CMJ. Motion capture and ground reaction force data were recorded and used as inputs to a musculoskeletal model. The muscular contributions COM acceleration were quantified with three separate induced acceleration analyses (i.e., unit-force, maximum-force, and absolute-force analysis). All three analyses suggest that (in rank order of magnitude) the soleus, gastrocnemii, and vastii muscles exhibited the largest contributions to COM acceleration during CMJ.